PHP and MySQL video training - Wandschneider, Marc.; Safari eBooks ([Upper Saddle River, NJ?] : Prentice Hall, 2008)
"In this one-of-a-kind video package, top Web developer and Prentice Hall author Marc Wandschneider shows you exactly how to build reliable, secure, industrial-strength Web applications with PHP and MySQL. You'll master both PHP and MySQL through 18 comprehensive video lessons, and you'll have your first PHP/MySQL application running in less than an hour. Wandschneider shows how to set up PHP on Windows and Mac OS X and then builds your skills by walking you through actual application development projects. Just click, watch, and learn efficient ways to implement user account creation, form validation, cookie and session management, file upload/download, and much more."--Resource description page.
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Title from resource description page (viewed March 10, 2009).
Electronic reproduction.
Keywords: PHP (Computer program language); MySQL (Electronic resource); Web site development; Electronic books